THE EFFECCT OF PAVER JOINT WIDTH ON THE CONSTRUCTION OF CONCRETE BLOCK PAVEMENT ON SLOPING ROAD SECTION - Rachmat Mudiyono (International Conference on Coastal and Delta Areas, 2015)
This research presents the construction of concrete block pavement (CBP) on sloping road section that influences the joint width between blocks. The effect of load transfer on the CBP behavior is discussed. The results of a series of tests conducted in laboratory with horizontal force test. The horizontal force testing installation was constructed within the steel frame 2.00 x 2.00 meter and forced from the side until CBP failure (maximum horizontal creep). The optimum joint width between blocks is 3 mm. For joint widths less than the optimum, the jointing sand was unable to enter inside between blocks. A large amount of sand remained outside the joint showing sand heaps on the block surface. The effect of the degree of slope on concrete block pavements on sloping road section area is significant with friction between blocks and thrusting action between adjacent blocks at hinging points is more effective with thicker blocks. The spacing of anchor beam will be increases with decreasing joint width.Keywords: Optimum, Joint width and Horizontal Creep.